INTERDISCIPLINARIEDAD Y TRIANGULACIÓN EN CIENCIAS SOCIALES - Arias Alpizar , Luz Mary (2009)
This article presents an argument about how triangulation plays a role on interdisciplinary research. It exposes that only the research practices and not the speech activities are the ones that can carry out a change in the Social Science paradigm. This leads into a previous discussion about the epistemological extents of the triangulation and interdisciplinarity on research.